Le repositionnement des éditoriaux des journaux municipaux face à la métropolisation - Marie Lyne Mangilli Doucé (Communiquer)
The article examines how the French territorial reforms of 2014 and 2015, which strengthened the Metropolises, are accompanied by a discursive repositioning of municipal institutional publications. The analysis of municipal newspaper editorials highlights the emergence of three municipal communication strategies. Whether they are "defensive and protective", "entrepreneurial" or "appropriative" , these strategy trends serve the legitimacy and normalization of the municipal political capacity to act, which is undermined by the government emergence of Metropolises and lead to a communicational disharmony on metropolitan territory.